Prince Claus Awards 2000. - Bharucha, Rustom; Diawara, Manthia; Field, Simon; Grimwood, Ashraf; Hamer, Sandra den; Hoet, Jan; Mohamad, Goenawan; Nasrallah, Yousry; Niehof, Anke; Serageldin, Ismail; Shankar, Ravi; Wang, Shuo; et al. (Den Haag : Prince Claus Fund, 2000)
The Principal 2000 Prince Claus Award was presented on 12 December 2000 at the Royal Palace in Amsterdam by HRH Prince Claus of the Netherlands.
boek
Keywords: Lerner, Jaime; Rio, Viva; Toledo, Francisco; Hasan Arif; Khakhar, Bhupen; Van Leo